The influence of genitalis odors to women’s life - Giraldo, Paulo Cesar; Amaral, Rose Luce do; Gonçalvez, Ana Katherine Silveira (Brazilian Journal of Sexually Transmitted Diseases, 2020)
Objective: To study current knowledge about genital odors by narrative review and suggest a scientifically validated approach to the problem. Methods: Narrative review taking into account articles published in the last 15 years. Results: Vaginal infections and/or dysbioses are the main causes of bad genital odor, with bacterial vaginosis (BV) being the most frequent finding. The change in the body’s smell can be caused by several factors that include everything from food to stress. As the cases of vaginal dysbioses are becoming more and more frequent and the treatments usually recommended do not always solve the problem, the use of vaginal acidifiers has become more recurrent to rebalance the vulvovaginal pH. Despite this, there is not yet a scientifically validated approach to identifying the cause of the odor. Conclusion: Female genital malodor affects women’s quality of life and should be investigated and treated accordingly.